Impact of the COVID-19 Pandemic on Peer Support Services in the Veterans Health Administration: Lessons for Healthcare Organizations - Johanne Eliacin; Alexandria N. Miller; Marianne S. Matthias; Diana J. Burgess; Scott Patterson; Caitlin E. O’Connor; Angela L. Rollins (Administration and Policy in Mental Health and Mental Health Services Research, 2026)
Abstract To identify strategies that faciliate the implementation adaptation of peer support services to ensure continuity and effectiveness of mental health care during crisis or rapid organizational changes. This is a cross-sectional, qualitative study that was conducted during the COVID-19 pandemic with a purposeful sample of Veterans Health Administration (VHA) peer specialists and their supervisors from 11 facilities in a Veteran Integrated Service Network (VISN). Data collection and analysis were guided by the Consolidated Framework for Implementation Research (CFIR). Deductive and inductive thematic analysis approaches were used to analyze the data. VHA peer specialists employed various strategies that incorporated multiple CFIR domains to adapt to the COVID-19 restrictions and rapid organizational changes. Findings indicate that peer specialists as key individuals involved in delivering and implementing peer support services, as well as higher-level, outer setting factors such as patients’ needs drove these adaptations. Some strategies and CFIR domains were more influential than others in shaping these adaptations. Three key strategies emerged as potentially useful in future public health crises and rapid organizational changes to expand the capacity of peer specialists’ role to meet patients’ healthcare needs: 1) adopting a work culture that is receptive to change (learning climate), 2) promoting collaboration (network and collaboration), and 3) fostering peer specialists’ self-efficacy (characteristics of the individual). During times of crisis, foundational organizational practices, such as change management techniques and transformational leadership styles, can help support service delivery adaptations and improve care delivery to patients.